Behavioral effects of ethanol in the Red Swamp Crayfish (Procambarus clarkii). Issue 3 (9th March 2022) - Gutierrez, Arnold; Creehan, Kevin M.; de Guglielmo, Giordano; Roberts, Amanda J.; Taffe, Michael A.
Abstract : Alcohol abuse remains one of the primary preventable sources of mortality in the United States. Model species can be used to evaluate behavioral and other biological changes associated with alcohol and to identify novel treatments. This report describes methods for evaluating the behavioral effects of ethanol (EtOH) in crayfish. Crayfish ( Procambarus clarkii ) were immersed in ethanol concentrations ranging from 0.1 to 1.0 molar, for 10‐30 min. Studies evaluated hemolymph alcohol concentration, locomotion in an open field and anxiety‐like behavior using a Light/Dark transfer approach. EtOH immersion produced dose‐dependent increases in hemolymph EtOH (up to 249 mg/dL) and reductions in open field locomotion that depended on EtOH concentration or exposure duration. Untreated crayfish exhibit avoidance of the open parts of the locomotor arena and a preference for a covered portion. Acute EtOH immersion decreased time spent in the covered portion of the Light/Dark arena, consistent with a decrease in anxiety‐like behavior. Daily EtOH immersion for 5 days did not alter locomotor responses, however, activity was increased 3 days after the repeated EtOH regimen. Overall, this study shows that this inexpensive, easily maintained species can be used for behavioral pharmacological experiments designed to assess the acute and repeated effects of EtOH.